Identification of molecular crystals capable of undergoing an acyl-transfer reaction based on intermolecular interactions in the crystal lattice - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Chemistry-A European Journal, 2013)
Investigation of the intermolecular acyl-transfer reactivity in molecular crystals of myo-inositol orthoester derivatives and its correlation with crystal structures enabled us to identify the essential parameters to support efficient acyl-transfer reactions in crystals: 1)the favorable geometry of the nucleophile (OH) and the electrophile (CO) and 2)the molecular assembly, reinforced by CH interactions, which supports a domino-type reaction in crystals. These parameters were used to identify another reactive crystal through a data-mining study of the Cambridge Structural Database. A 2:1 co-crystal of 2,3-naphthalene diol and its di-p-methylbenzoate was selected as a potentially reactive crystal and its reactivity was tested by heating the co-crystals in the presence of solid sodium carbonate. A facile intermolecular p-toluoyl group transfer was observed as predicted. The successful identification of reactive crystals opens up a new method for the detection of molecular crystals capable of exhibiting acyl-transfer reactivity.
Keywords: Acylation; domino reactions; intermolecular interactions; solid-state reactions; X-ray diffraction

Acyl-transfer reactions in molecular crystals: reactivity correlation with crystal structure - Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: crystal engineering; intermolecular interactions; solid-state reactions

Experimental and theoretical charge density, intermolecular interactions and electrostatic properties of metronidazole - Kalaiarasi, Chinnasamy; George, Christy; Gonnade, Rajesh G.; Hathwar, Venkatesha R.; Poomani, Kumaradhas (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2019)
Metronidazole is a radiosensitizer; it crystallizes in the monoclinic system with space group P2(1)/c. The crystal structure of metronidazole has been determined from high-resolution X-ray diffraction measurements at 90 K with a resolution of (sin 0/lambda) max = 1.12 angstrom(-1). To understand the charge-density distribution and the electrostatic properties of metronidazole, a multipole model refinement was carried out using the Hansen-Coppens multipole formalism. The topological analysis of the electron density of metronidazole was performed using Bader's quantum theory of atoms in molecules to determine the electron density and the Laplacian of the electron density at the bond critical point of the molecule. The experimental results have been compared with the corresponding periodic theoretical calculation performed at the B3LYP/6-31G** level using CRYSTAL09. The topological analysis reveals that the N-O and C-NO2 exhibit less electron density as well as negative Laplacian of electron density. The molecular packing of crystal is stabilized by weak and strong inter- and intramolecular hydrogen bonding and H center dot center dot center dot H interactions. The topological analysis of O-H center dot center dot center dot N, C-H center dot center dot center dot O and H center dot center dot center dot H intra- and intermolecular interactions was also carried out. The electrostatic potential of metronidazole, calculated from the experiment, predicts the possible electrophilic and nucleophilic sites of the molecule; notably, the hydroxyl and the nitro groups exhibit large electronegative regions. The results have been compared with the corresponding theoretical results.
Keywords: atomic valence index; Electron density; Electrostatic potential; intermolecular interactions; metronidazole; radiosensitizer

Investigation of bond topological and electrostatic properties of plumbagin molecule: an experimental and theoretical charge density study - Kalaiarasi, Chinnasamy; Sivanandam, Magudeeswaran; Suganya, Suresh; Christy, George; Gonnade, Rajesh G.; Hathwar, Venkatesha R.; Kumaradhas, Poomani (Journal of Molecular Structure, 2020)
Plumbagin is a naturally occurring derivative with several medicinal properties including antioxidants, antifungal, antimalarial, leprosy and antitumor properties; their structural and electrostatic properties are yet to be determined. The crystal structure of plumbagin has been solved; it shows that the compound crystallizes in P2(1)/c space group with two molecules in the asymmetric unit. The electron density distribution of both molecules have determined from multipole model refinement. Among all the C-O bonds of both molecules (I & II), the OH group connected C-O bond and the methyl group connected C-C bond exhibits less electron density and the negative Laplacian of electron density as well. Further, the electrostatic potential (ESP) surface of two plumbagin molecules show some difference in their electronegative regions. The carbonyl O-atoms exhibit high electronegative ESP regions which are the key reactive locations of plumbagin when bind with the active site of target protein and in the ESP map, an aromatic pi-cloud also observed in one of the molecule. The electron density distribution of O-H center dot center dot center dot O intermolecular interactions between the molecules I and II, reveals that these interactions are found very stronger than the other interactions in the crystal. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Dipole moment; Electron density; Electrostatic potential; intermolecular interactions; Plumbagin

Construction of two-component chemically reactive supramolecular assemblies-acyl migration reactions in cocrystals of napthalene-2,3-diol and its diesters - Bahadur, Vir; Gonnade, Rajesh G.; Tamboli, I. Majid; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (ChemPlusChem, 2021)
Reactions in solids are of contemporary interest due to applications in pharmaceutical industries to environmental sustainability. Although several reactive crystals that support chemical reactions have been identified and characterized, the same cannot be said about reactive cocrystals. Earlier we correlated the facile acyl group transfer reactions in crystals with supramolecular parameters obtained from the crystal structures. The structure-reactivity correlation revealed the requirement of proper juxtaposition of electrophile (C=O) and the nucleophile (OH) with distance (similar to 3.2 angstrom) and angle (similar to 90 degrees) along the chain structure. The current article describes the preparation of cocrystals that are capable of supporting intermolecular acyl group transfer reactions in a group of structurally similar molecules. The cocrystals of naphthalene 2,3-diol and its corresponding diesters showed a facile solid state acyl transfer reaction, which has been well correlated with their crystal structures.
Keywords: Acylation; domino reactions; intermolecular interactions; reaction in cocrystal; solid-state reactions; X-ray diffraction